Evaluasi perencanaan, pelaksanaan, penatausahaan, pelaporan dan pertanggungjawaban pengelolaan keuangan APBDesa berdasarkan Permendagri Nomor 20 Tahun 2018 (Studi kasus di Desa Toiba Kecamatan Bualemo Kabupaten Banggai) - Delia Selviana Mamangkey; Jantje J. Tinangon; Novi Swandari Budiarso (Yayasan Widyantara Nawasena Raharja, 2023)
The Village Revenue and Expenditure Budget has a significant impact on the development of the village. It is therefore crucial that the APBDesa is managed effectively and in accordance with government procedures. This study aims to assess the financial management process in Toiba Village, Bualemo District, and its alignment with Permendagri Number 20 of 2018. The research used descriptive qualitative methods and analysed the data using comparative analysis techniques. The findings indicate that the management of the APBDesa in Toiba Village is in line with Permendagri Number 20 of 2018. However, it is important to ensure regular support and training from the sub-district government to the village government during the planning, management, and reporting phases. In addition, the supervisory team needs to be strengthened to ensure that the implementation of development in the village is in line with the development plans. Regular evaluations of the APBDes management are also necessary to ensure that any discrepancies are immediately corrected by the village government and that the financial management of the APBDesa complies with Government Regulation No. 20 of 2018.